Can anyone help me with this?

$\displaystyle 3=\frac{1}{(x+1)^2} + \frac{2}{(x+1)}$

I sub $\displaystyle u={(x+1)^-1}$

then flip them and rearrange so I get $\displaystyle u^2+\frac{u}{2}-3=0$

then mutiply all by two to get rid of fraction.

then I factor and end up with $\displaystyle (2u-3)(u+2)=0$

I think the problems begin when I sub back in the $\displaystyle {(x+1)^-1}$... doing something wrong and not getting book's solutions.

btw those -1's are supposed to be superscripted, not sure why its not working :/